2002
DOI: 10.1053/rmed.2002.1282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of second controller medications in addition to inhaled corticosteroid in patients with moderate asthma

Abstract: The objective of this study was to compare the efficacy and safety of the second controller medications (long-acting beta2-agonist, leukotriene receptor antagonist and sustained-release theophylline) used in addition to inhaler corticosteroid treatment in moderate persistent asthma. A total of 64 patients with asthma, in the moderate persistent asthma category, were divided into three groups. Patients, all of whom were concurrently using inhaled corticosteroid (Budesonide 400 microg twice daily), were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
0
31
1
1
Order By: Relevance
“…No signifi cant inter-study heterogeneity was found (I 2 =0, p=0.80). Mean change in number of daily short β 2 -agonist use: 166 patients from three studies were considered for this analysis (82 treated with ICS plus LTRA, 84 treated with ICS plus theophylline) (Yurdakul et al, 2002;Tsuchida et al, 2005;Shah et al, 2006). There was no signifi cant difference between ICS plus LTRA and ICS plus theophylline therapy in reducing the number of dailyβ2-agonist use in asthmatics (mean difference 0.04 [95% CI -0.30-0.38], p=0.82) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…No signifi cant inter-study heterogeneity was found (I 2 =0, p=0.80). Mean change in number of daily short β 2 -agonist use: 166 patients from three studies were considered for this analysis (82 treated with ICS plus LTRA, 84 treated with ICS plus theophylline) (Yurdakul et al, 2002;Tsuchida et al, 2005;Shah et al, 2006). There was no signifi cant difference between ICS plus LTRA and ICS plus theophylline therapy in reducing the number of dailyβ2-agonist use in asthmatics (mean difference 0.04 [95% CI -0.30-0.38], p=0.82) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…No signifi cant interstudy heterogeneity was found (I 2 =0, p=0.56). Asthma exacerbations: Data on asthma exacerbations were available in two trials (49 treated with ICS plus LTRA, 50 treated with ICS plus theophylline) (Yurdakul et al, 2002;Shah et al, 2006). Asthma exacerbations were almost equal between ICS plus LTRA and ICS plus theophylline therapy in asthmatics (pooled OR 1.00 [95% CI 0.23-4.38], p=1.00) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of the asthma symptom score is one of the most important outcome measure reported by the patients in order to assess, their feeling about asthma [19,20]. Both day-time and night-time asthma symptom scores will be noted.…”
Section: Asthma Symptom Scoresmentioning
confidence: 99%